PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MERANCANG PEKERJAAN KARYAWAN PADA PT. PERTANI (PERSERO) WILAYAH SULAWESI - Fadila S, Nurjannah; Marhumi, Sitti; Zalkha Soraya; Nurinaya (Jurnal Bisnis dan Kewirausahaan, 2024)
This study aims to determine the role of human resource management in designing the work of employees at PT Pertani (Persero) Sulawesi Region. This study uses qualitative research by looking at the role of HR in Designing Employee Jobs at PT. PT Pertani (Persero) Sulawesi Region. And the analysis technique used is analyzing the data, reducing the data, compiling the results of data reduction, presenting the data and checking the validity of the data and drawing conclusions. The results of the study indicate that human resource management plays an important role in the continuity of the company's running, so that Human Resource Management (HR) must ensure that the company has a reliable workforce which is carried out when designing employee jobs because Human Resource Management is fairly important in determining factors of production. , building and in developing the company. The design that has a strategic impact on employees has been made by the management, namely, HR management in accordance with the company's needs, training to increase insight and product introduction to all employees and awards for employees who are dedicated to the company. The strategy that can be done in developing human resources is that employees must be updated with the times. Keep up with every technological development so we don't miss out. And conduct training for employees.